ANALYSIS OF THE PROPOSED AIRSPACE STRUCTER OF MOSCOW ATM - N. I. Divak; E. E. Nechaev (Научный вестник МГТУ ГА, 2016)
The article deals with the aspects of construction of a new airspace structure of the Moscow ATM the major «weak points" of the proposed structure are identified and analyzed an alternative way of settling disputes are provided.